2012
DOI: 10.1111/j.1365-2966.2012.20886.x
|View full text |Cite
|
Sign up to set email alerts
|

Star formation activities in early-type brightest cluster galaxies

Abstract: We identify a total of 120 early-type Brightest Cluster Galaxies (BCGs) at 0.1 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 87 publications
18
60
0
Order By: Relevance
“…Furthermore, some BCGs show low levels of star formation in the local Universe (e.g. Liu et al 2012;Oliva-Altamirano et al 2014;Fraser-McKelvie et al 2014). This is consistent with the hypothesis that BCGs have complex accretion scenarios.…”
Section: Merger Historiessupporting
confidence: 74%
“…Furthermore, some BCGs show low levels of star formation in the local Universe (e.g. Liu et al 2012;Oliva-Altamirano et al 2014;Fraser-McKelvie et al 2014). This is consistent with the hypothesis that BCGs have complex accretion scenarios.…”
Section: Merger Historiessupporting
confidence: 74%
“…In addition, we show the star formation rates determined by Liu et al (2012) for a sample of central cluster galaxies from SDSS, and those of McDonald et al (2015) for BCGs of SPT clusters. When comparing with the limit below Figure 11.…”
Section: Star Formation Ratesmentioning
confidence: 99%
“…Galaxies with no detectable star formation in the previous 500 Myr have been assigned random values between 10 −3 and 10 −2 M /yr. For comparison, the main sequence of star forming galaxies in SDSS from Woo et al (2013) (solid black line) and the division between star-forming and quenched galaxies (black dotted) along with the OII-derived star formation rates for the BCG samples of Liu et al (2012) and the UV estimates of McDonald et al (2015) are shown (note that for the latter, data points with only long lower error bars are upper limits).…”
Section: Star Formation Ratesmentioning
confidence: 99%
“…This simple parameter has been shown to robustly identify AGN-driven radio activity as being characterised by a q24 value of less than −0.16 (e.g., Norris et al 2006;Middelberg et al 2008;Mao et al 2012), and therefore relative radioloudness, largely independent of the redshift of the emission or the host galaxy contribution (Appleton et al 2004;Wilkes et al 2009;Sargent et al 2010;Mao et al 2011;Hales et al 2014). While a single-band radio analysis does not afford a complete characterisation of the radio properties of the BCGs in our sample -e.g., to determine the number, character, physical size, or age of the distinct radio components which may be associated with the BCGs (Hogan et al 2012) -the q24 parameter offers an additional, reliable means by which to determine the fraction of BCGs in our sample with a dominant AGN.…”
Section: Mid-infrared Radio Correlationmentioning
confidence: 99%